ANALISIS MANAJEMEN PIUTANG PENJUALAN KAMAR HOTEL DEKA - Sulistiana, Heny; Suhartini, Dwi (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
Receivables are an important component that can affect cash flow, so proper receivables management is needed to increase sales volume and prevent the risk of default. Form credit facility Letter is a policy implemented by hotels before providing credit facilities to debtors. This research uses a qualitative approach with a descriptive type, data is collected to provide an overview of conditions and issues related to problems that require detailed information. Receivables management to increase room sales is collaborating with wholesalers and corporates, although this is not optimal, but is an effort to introduce and reach a larger market share which can increase the company's receivables through credit sales.